Pengaruh Brand Ambassador BTS (Bangtan Boys) dan E-Trust terhadap Minat Beli - Laras Tri Ayu (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The large amount of e-commerce users in Indonesia has made Marketplace as one of the biggest players in the most popular e-commerce business nowadays. This opportunity used by big companies to compete to attract people's purchase interest in Indonesia. In order to growing purchase interest on marketplace requires a high sense of trust and strong promotion using brand ambassadors to disseminate information and attract consumers to create a sense of trust for making purchases. The purpose of this study is to determine how much the relationship and affect of BTS as brand ambassadors and e-trust on puchase interest. The object of this research is the community of Tokopedia Marketplace users on social media. The data collection technique used is the Questionnaire, Observation and Literature technique. The results show that there is a correlation between brand ambassadors and e-trust for 0.677, there is a partial effect of brand ambassadors on purchase interest for 0.142, there is a partial effect of e-trust on purchase interest for 0.528, there is a simultaneous affect of brand ambassadors and e-trust on purchase interest for 0.670.